Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Ukuran Perusahaan, Profitabilitas dan Leverage terhadap Nilai Perusahaan - Fajar Ahmad Aryanto; Mujino Mujino; Risal Rinofah (Jurnal Ilmiah Manajemen dan Bisnis, 2020)
This research is proposed to find the influence of managerial ownership, institutional ownership, firm size, profitability and leverage on firm value in manufacturing companies in the consumer goods industry sector in the Indonesian stock market. This research used a quantitative approach. The population of the company in this study is the consumer goods industry sector in the Indonesian stock market in 2014-2018. The technique used to take samples uses purposive sampling. Data analysis techniques used multiple linear regression, partial test, simultaneous test and coefficient of determination.